2013
DOI: 10.1155/2013/698205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Different Doses of Gabapentin on the Intraocular Pressure and Hemodynamic Stress Responses to Laryngoscopy and Tracheal Intubation

Abstract: Background. The stress response to laryngoscopy and intubation causes an undesirable increase in heart rate, blood pressure, and intraocular pressure. This study was designed to compare the effect of two doses of gabapentin on the stress response to laryngoscopy and intubation. Patients and Methods. (ASA I and II) 60 patients, aged from 18 to 60 years undergoing elective eye surgery requiring endotracheal intubation, were randomly allocated into 3 groups, 20 patients each. 2 hours before the surgery, group I r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The mechanism of action being suggested for cardiovascular changes mediated by calcium channel blockade and reduction of plasma catecholamines is still unclear (22). In another study, different doses of gabapentin, used to attenuate hemodynamic changes during orotracheal intubation were compared with a reduced response (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action being suggested for cardiovascular changes mediated by calcium channel blockade and reduction of plasma catecholamines is still unclear (22). In another study, different doses of gabapentin, used to attenuate hemodynamic changes during orotracheal intubation were compared with a reduced response (23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-emptive single dose gabapentin inhibited hyperalgesia development for 2 days in an animal study for post-operative pain, however when administered 1 h after the intervention, it decreased symptoms only for 3 h.[ 7 ] In this study, we chose gabapentin dose of 1.2 g, which is within the limit of single daily dose, as that used for neuropathic pain treatment ranging from 900 to 1200 mg three times a day and after reviewing the doses used in previous studies. [ 14 15 16 ]…”
Section: Discussionmentioning
confidence: 99%
“…In humans 12 and dogs, 18 gabapentin has been utilised to prevent the elevation of IOP caused by endotracheal intubation. It has been reported that gabapentin administration is associated with reduced IOP levels in elderly patients undergoing intraocular surgery 13 .…”
Section: Discussionmentioning
confidence: 99%